1983
DOI: 10.1177/009286158301700309
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Computerized Drug Interaction Database (Medicomsm) for Use in a Patient Specific Environment

Abstract: Drug Interactions are a clearly defined problem that we as health professionals must deal with on a day-by-day basis. It is by far the area of health care that demands more attention today and tomorrow than was possible in the past. The amount of reference sources and text material of drug interactions is growing at such a rate that it is almost impossible to recall essential information in a reasonable time frame. If the practitioner is to continue with an uninterrupted work flow and still maintain the best p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
2

Year Published

1987
1987
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 1 publication
1
5
0
2
Order By: Relevance
“…This is similar to the findings of other studies that reported 37% to 60% of patients having pDDIs on hospital admission [8][9][10][11][12].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is similar to the findings of other studies that reported 37% to 60% of patients having pDDIs on hospital admission [8][9][10][11][12].…”
Section: Discussionsupporting
confidence: 91%
“…ADRs can result from the action of a single drug or from a drug-drug interaction (DDI) [5][6][7]. Recent studies have shown that 37-60% of patients are taking drugs with potential DDI (pDDI) on hospital admission [8][9][10][11][12] and 41-69% on hospital discharge [13][14][15][16]. A 2007 literature review of hospital admissions due to DDI showed that DDIs accounted for 0.6% of all admissions to hospitals with different specialist departments [17].…”
Section: Introductionmentioning
confidence: 99%
“…Drug interactions are important because they can cause adverse drug reactions in patients receiving multi‐drug therapy. Numerous articles (1–5) have described methods for screening for potential drug interactions using medical records of prescriptions in order to effectively prevent any further adverse drug‐related outcomes. As not all potential drug interactions are clinically significant, especially with proper management, any observed clinical drug interaction is most important because it has a real impact on the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacokinetics of doxa pram in premature infants have been re ported only in the presence of theophylline [5, 6, 10, 11]. However, theophylline is known to alter the pharmacokinetics of many drugs [7], The intention of this study was to determine whether such an interac tion exists between the two drugs. We now report the pharmacokinetics of doxapram given before or after a course of theophylline therapy.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the interaction of theophylline with several other drugs produces a variety of results. For example, it has been reported that theophyl line could be responsible for the reduced plasma concentration of phenytoin and lith ium [7]. Theophylline has also been sus pected of causing resistance to pancuro nium-induced neuromuscular blockade [7], Being a diuretic agent, theophylline may also be capable of interfering with the renal clear-…”
Section: Introductionmentioning
confidence: 99%